PEMANFAATAN MEDIA PEMBELAJARAN GAME INTERAKTIF DALAM PEMBELAJARAN KOSAKATA BAHASA ARAB - Muhammad Luqman Hakim (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
Arabic language is one of the areas of study taught at the level of junior high school. Learning of Arabic language on the this level directed at the fourth skill, there are; listening skills (Al-maharah Al-Istima’), speaking skills (Al-maharah Al-Kalam, reading skills Al-Maharah Al-Qira’ah), and writing skills (Al-Maharah Al-Kitabah).The fourth skill cannot be achieved without having a good mastery of vocabulary, because the quality of a person's language skills depends on the quantity and quality of its own vocabulary. This research aims to obtain information about the needs of the media in learning Arabic language. The method used is qualitative descriptive and review of the literature. The results of this research is in the Arabic language learning requires media interactive games to make learning interesting and can facilitate the learning process.